HUBUNGAN IBU HAMIL PENGIDAP DIABETES MELLITUS DENGAN KELAHIRKAN BAYI MAKROSOMIA DI RSAB HARAPAN KITA JAKARTA - Heru Setiawan; Yudhia Fratidhina; Mohammad Ali (Poltekkes Kemenkes Jakarta III, 2014)
Diabetes Mellitus (DM) is a collection of symptoms that occur in a person due to insufficient insulin hormone that can not work normally. DM can cause a variety of complications, and complications can also occur in pregnant women. Pregnant women who suffer from diabetes more likely to deliver larger babies (macrosomia). This can complicate the birth process may cause trauma of birth, even newborns having weight above the normal value can not cry or breathe spontaneously at birth or a regular basis. If this condition persists, the future can cause birth defects. If this condition can lead to prolonged mental or physical disability. This study aims to determine the percentage of pregnant women living with diabetes who delivered macrosomic infants. This research is a descriptive cross sectional study, the secondary data retrieval by record number of 100 medical records of pregnant women living with diabetes and non-diabetes who delivered macrosomic infants in RSAB Harapan Kita Jakarta during the period 2010-2011.The results showed the average age of pregnant women living with DM 33.5 years, gestational age 38.5 weeks, while glucose 167.5 mg / dL and the percentage of pregnant women living with diabetes with macrosomic infants born in RSAB. Harapan Kita Jakarta is 44.8%. DMG case in RSAB Harapan Kita Jakarta, prevalence was only 1.2%.There is no association between gestational diabetes mellitus with macrosomia (p-value 0.301)